2018
DOI: 10.2174/1566524018666180222121643
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Protects SH-SY5Y Cells from OGD/RInduced Injury

Abstract: The present study demonstrated that exogenous H2S exerts a protective effect against OGD/R-induced injury by enhancing the activation of the ERK3, p38MAPK and Nrf2 mRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Thus, inhibiting or regulating the expression and activity of MAPK signalings may constitute novel therapeutic strategies for CIRI (36, 37). Recent studies have found that several drugs might play protective roles in CIRI by inhibition of MAPK signaling pathways (38, 39). The MAPK family includes extracellular signal-regulated kinase 1/2 (ERK1/2), c-Jun amino terminal kinase (JNK) and p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibiting or regulating the expression and activity of MAPK signalings may constitute novel therapeutic strategies for CIRI (36, 37). Recent studies have found that several drugs might play protective roles in CIRI by inhibition of MAPK signaling pathways (38, 39). The MAPK family includes extracellular signal-regulated kinase 1/2 (ERK1/2), c-Jun amino terminal kinase (JNK) and p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since SH‐SY5Y cells are human‐derived, they express several human‐specific proteins and isoforms that would not be inherently present in rodent primary cultures 14,15 . Particularly, this cell line is used to develop the in vitro OGD/IR model 15‐21 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Particularly, this cell line is used to develop the in vitro OGD/IR model. [15][16][17][18][19][20][21] Current findings in regenerative medicine have strengthened the search for new stem cell sources with beneficial properties; in particular, amniotic fluid has been identified as a valid resource of stem cells in this field. Adult stem cells, even after reprogramming, could preserve epigenetic alterations, thus representing a limitation in their application.…”
Section: Introductionmentioning
confidence: 99%
“…The OGD/R model is a cell injury model extensively applied in the investigation of CIR injury in vitro [18, 22, 23]. Initially, we established an in vitro model of CIR injury subjected to OGD/R treatment.…”
Section: Discussionmentioning
confidence: 99%